The Power of directors: Do multiple job, military connection, political connection determine firm value mining sector coal production? - Diarta, Anggy; Sri Yuni; Golda Belladonna Umbing; Agus Satrya Wibowo; Fitria Husnatarina; Ade Yuniati (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2025)
This study aims to examine the influence of Multiple Job, Military Connection, and Political Connection of the CEO on Firm Value, with Company Size and Leverage as control variables. The population in this study is coal production sector mining companies listed on the Indonesia Stock Exchange from 2020-2022. The sampling technique used purposive sampling with the criteria being companies that issued financial statements & annual reports consecutively from 2020-2022. The reason for choosing this sector is because it is growing day by day, and it is directly regulated by the government. Based on these criteria, 23 coal production sector mining companies were selected as samples, resulting in 69 observations conducted in this study. The research analysis technique used panel data method. Data were processed using E-Views 10 software. The results of the study indicate that multiple job do not affect firm value. Military connection have a positive influence on firm value. Political connection do not affect firm value